2018
DOI: 10.11591/edulearn.v12i1.7045
|View full text |Cite
|
Sign up to set email alerts
|

The Obstacles and Strategy of Project Based Learning Implementation in Elementary School

Abstract: This study aims to: 1) examine the challenges teachers encounter in implementing project-based learning in 2013 curriculum, 2) to examine teachers' strategies in integrating project-based learning in 2013 curriculum. This research finds several obstacles faced by teachers and strategies that can be done in the implementation of project-based learning, they are: 1) the obstacle in terms of students' capability can be overcome by familiarizing them to complete projects; 2) the obstacle in terms of indiscipline c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 8 publications
3
10
0
4
Order By: Relevance
“…This was because some of the students whom had found PBL to be 'repetitive' and 'boring' mentioned that the PBL approach had given them the opportunity to be 'creative' in terms of how they presented their learning to their peers. In other words, they reported that the information they obtained through the PBL approach were 'different from those in the textbook' [21], [25]- [30]. In addition, the students mentioned that PBL gave them the chances to work collaboratively with their friends.…”
Section: Effects Of Motivation and Collaboration On Students' Learningmentioning
confidence: 99%
See 3 more Smart Citations
“…This was because some of the students whom had found PBL to be 'repetitive' and 'boring' mentioned that the PBL approach had given them the opportunity to be 'creative' in terms of how they presented their learning to their peers. In other words, they reported that the information they obtained through the PBL approach were 'different from those in the textbook' [21], [25]- [30]. In addition, the students mentioned that PBL gave them the chances to work collaboratively with their friends.…”
Section: Effects Of Motivation and Collaboration On Students' Learningmentioning
confidence: 99%
“…Most of the concerns brought forward by these researchers were that teachers were reluctant to move from the use of the traditional approaches as they were more comfortable with the idea of having control over the classroom [19], [20]. Research has highlighted that students were in fact the ones who had preferred the use of the traditional approach as they were uncomfortable with the idea of having to obtain knowledge on their own [21]. Even high achiever students were reluctant with the use of PBL as they felt that collaborative learning was a burden for them when they have free riders in their groups [22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed differences from previous research, namely: research trends in project-based biology learning increased in 2015-2017 and decreased until 2022. This was due to several obstacles in its implementation such as students being less accustomed to completing projects, indiscipline, limited time, and limited equipment so teachers must have confidence and commitment in implementing project-based learning (Cintang, 2019). In addition, Le (2021) stated that teamwork is a difficult thing experienced by students in project work.…”
Section: Pjbl Studies Assess Science Skillsmentioning
confidence: 99%